Vaccination in pregnancy against pertussis and seasonal influenza: key learnings and components from high-performing vaccine programmes in three countries: the United Kingdom, the United States and Spain - Théophile Baïssas; Florence Boisnard; Inmaculada Cuesta Esteve; Marta Garcia Sánchez; Christine E. Jones; Thierry Rigoine de Fougerolles; Litjen Tan; Olivier Vitoux; Christina Klein (BMC, 2021)
Abstract Background Pertussis and seasonal influenza are responsible for significant maternal, neonatal, and infant morbidity and mortality, but vaccine coverage rates (VCR) for both pertussis (administered as a tetanus, diphtheria, acellular pertussis [Tdap] vaccination) and seasonal influenza in pregnancy remain generally low. Only a small number of countries, including Spain, the United Kingdom (UK), and the United States (US), have high Tdap and seasonal influenza VCRs in pregnancy. The purpose of this study was to identify the key factors that contributed to the high VCRs observed in these countries. Methods The experience from both Tdap and seasonal influenza vaccination programmes during pregnancy were documented in Spain, the UK, and the US using a three-step approach. A literature review yielded 157 publications, and a further 117 documents were selected through desk research. A published five-pillar VCR framework for influenza was amended to evaluate the specific contributing factors leading to high Tdap and seasonal influenza VCRs among pregnant women. Results The analysis identified components that contributed to higher VCR in pregnant women across three different healthcare systems in Spain, UK, and US. The combination of several key interventions in each country led to a rapid increase in VCR that reached near-optimal levels (i.e. 75% for seasonal influenza) within a few years. As well as inclusion in national immunisation programme and vaccine reimbursement, key components that were identified included the mobilisation of health authorities, prenatal care Healthcare Professionals (HCP) and scientific societies, the inclusion of vaccination in antenatal medical guidance, the provision of educational material to HCPs, and a strong disease awareness driven by recent pertussis outbreaks in each country. Conclusions Although there is no simple, universal solution to improving sub-optimal VCRs, the list of components identified in this study from three countries with high-performing Tdap and seasonal influenza vaccination programmes provides a basis for public health and medical stakeholders in other countries to define strategies to successfully implement national vaccination programmes for pregnant women.